Systematic Review of Evaluations of Trauma-Informed Organizational Interventions That Include Staff Trainings. (October 2020) - Purtle, Jonathan
Enthusiasm for trauma-informed practice has increased dramatically. Organizational interventions that train staff about trauma-informed practice are frequently used to promote trauma-informed systems change, but evidence about these interventions' effects has not been integrated. A systematic review was conducted of studies that evaluated the effects of organizational interventions that included a "trauma-informed" staff training component. A search was conducted in July 2017 and studies were identified in PubMed, PsycINFO, and the Published International Literature on Traumatic Stress database, limited to articles published in English after 2000. Six hundred and thirty-two articles were screened and 23 met inclusion criteria. Seventeen studies used a single group pretest/posttest design, five used a randomized controlled design, and one used a quasi-experimental design with a nonrandomized control group. The duration of trauma-informed trainings ranged from 1 hr to multiple days. Staff knowledge, attitudes, and behaviors related to trauma-informed practice improved significantly pre-/posttraining in 12 studies and 7 studies found that these improvements were retained at ≥1month follow-up. Eight studies assessed the effects of a trauma-informed organizational intervention on client outcomes, five of which found statistically significantly improvements. The strength of evidence about trauma-informed organization intervention effects is limited by an abundance of single group, pretest/posttest designs with short follow-up periods, unsophisticated analytic approaches, and inconsistent use of assessment instruments. In addition to addressing these methodological limitations, priorities for future research include understanding intervention effects on clients' perceptions of care and the mechanisms through which changes in staff knowledge and attitudes about trauma-informed practice influence client outcomes.